Cuban School Dictionaries for First-Language Learners: A Shared Experience - Tarp, Sven; Ruiz Miyares, Leonel (Lexikos, 2013)
One of the reasons why many publishing houses hesitate when allocating resources to the development of more advanced concepts of school dictionaries for first-language learners is the relatively poor sales and corresponding profits coming from this category of dictionaries. A major challenge is therefore how to change the situation, stimulate the use and sales of school dictionaries, and guarantee the necessary investment in product development. This contribution will take up this challenge. It will give no final answer, but it will discuss an experience with a Cuban school dictionary which has reached its target users in large numbers. The contribution will particularly look at the multi-faceted relation between lexicographers and users which characterises the Cuban dictionary project. The objective is not to copy this or any other experience but to inspire lexicographers looking for alternative solutions to a problem which is affecting both school children and lexicographers in many countries and language communities.